Disaster Resilient Village Program: Manifestation of Community-Based Disaster Risk Management and Reduction Policy - Freddy Johanis Rumambi; Dwi Novita Sari; Diana Ari Utami (International Journal of Sustainability in Research, 2023)
The potential and risk of disasters in Indonesia over the last two decades have become a major challenge for this country. Dynamic natural activities, global climate change, and rapid urbanization have increased vulnerability to various types of natural and man-made disasters. Although this risk cannot be completely avoided, mitigation efforts, risk management and community empowerment have been carried out to reduce its impact. The Disaster Resilient Village Program is one of the Indonesian government's important efforts to reduce disaster risk and increase community resilience. Although there are still challenges and obstacles that must be overcome, this program has provided significant benefits in preparing communities to face the threat of disaster.